Randomized Controlled Trial of a Computerized Interactive Media-Based Problem Solving Treatment for Depression. Issue 3 (May 2017) - Sandoval, Luis R.; Buckey, Jay C.; Ainslie, Ricardo; Tombari, Martin; Stone, William; Hegel, Mark T.
Abstract: This study evaluated the efficacy of an interactive media-based, computer-delivered depression treatment program (imbPST) compared to a no-treatment control condition (NTC) in a parallel-group, randomized, controlled trial conducted in an outpatient psychiatric research clinic. 45 adult participants with major depressive disorder or dysthymia were randomized to receive either 6 weekly sessions of imbPST or no treatment (No Treatment Control; NTC). The primary outcome measure was the Beck Depression Inventory II (BDI-II). There was a significant Group x Time interaction effect [ F (1.73, 43)= 58.78; p < .001; η2 = .58, Cohens d = 1.94], such that the patients receiving imbPST had a significantly greater reduction in depressive symptoms compared to the patients in the NTC condition. Participants in the imbPST group improved their depression symptoms significantly from moderate (BDI-II = 21.9 ± 4.20) to mild levels of depression (BDI-II = 17.9 ± 4.0) after receiving 3 weekly sessions of imbPST (p < 0.001), and progressed to still milder levels of depression after six weekly sessions (BDI-II = 14.5 ± 3.7, p < 0.001). NTC participants showed no significant reduction in BDI-II scores (BDI-II = 21.8 ± 4.2 pre, BDI-II = 21.5 ± 5.2 post, N.S.). Additionally, 40% of the imbPST group showed a clinically significant and reliable change in depression levels while none of the NTC group met this criterion. imbPST participants rated the program highly usable on the system usability scale (SUS) after the first session (SUS Session 1 = 74.6 ± 7.2) and usability scores increased significantly by the last session (SUS Session 6 = 85.4 ± 5.6). We conclude that imbPST is an effective, engaging, and easily used depression treatment program that warrants further evaluation with heterogeneous depressed populations in a stand-alone, self-administered fashion. Graphical Abstract: The imbPST program includes a mentor who guides the user through the program, and provides feedback based on user choices. In the picture below the mentor (Mark T. Hegel, Ph.D.) provides feedback on the PHQ-9 score Figure copyright ©Cartreine et al., 2012 . Originally published in JMIR Research Protocols (http://www.researchprotocols.org ), 25.09.2012. Highlights: Clinical trial of interactive-media-based problem-solving treatment for depression. This program had been shown to score highly on usability and therapeutic alliance. Twenty-five subjects using imbPST were compared with 20 that had no treatment. Depression symptoms improved significantly in the imbPST group. imbPST offers a usable, scalable method for providing effective depression treatment.